Islamic Public Finance Management Model In Muslim Countries: A Comparative Study of Zakat and Waqf in Saudi Arabia, Malaysia, Indonesia, and Pakistan - Dea Rodiah Luthfy; Nuralika Yepsi Sarmilantiva Said; Dwi Suci Widiastuti; Teti Maulina Dimyati (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2026)
Public financial management in Islam is fundamentally aimed at achieving distributive justice and social welfare based on the principles of maqāṣid al-sharī'ah. However, its implementation across Muslim countries demonstrates varying models shaped by their respective political, economic, and institutional contexts. This article aims to examine the models of Islamic public finance management, particularly zakat and waqf, in several Muslim countries, including Saudi Arabia, Malaysia, Indonesia, and Pakistan, with a focus on instruments, institutional frameworks, and their integration with national fiscal systems. This study employs a qualitative method with a descriptive-comparative approach through literature review and analysis of secondary empirical data. The data are derived from official documents such as annual reports of zakat and waqf institutions, government regulations, publications from international organizations, and previous scholarly works. Due to time constraints, field validation through surveys or interviews was not conducted. Instead, a desk-based case study approach was applied by analyzing documented practices of zakat and waqf management, including reports from Indonesia's National Zakat Agency (BAZNAS), waqf management publications in Malaysia, and zakat policy documents in Pakistan. This approach enables the study to maintain empirical validity through verified secondary data, despite the absence of primary data collection. The findings indicate that most Muslim countries adopt a hybrid model by integrating Islamic public finance principles with conventional fiscal systems. Nevertheless, such integration remains partial, as taxation continues to serve as the primary source of state revenue, while zakat and waqf are managed by specialized institutions outside the core fiscal system. Therefore, this article recommends the development of an integrated Islamic public finance model based on maqāṣid al-sharī'ah to enhance social justice and improve the effectiveness of public resource distribution.